Evaluation of the e-learning service quality at the Algerian university during the corona pandemic from the point of view of a sample of university students - Mohamed Yacine Hamdi (Dirassat Journal Economic Issue, 2023)
This study aims to find out the quality level of the e-learning service, which Algerian universities relied on, as an auxiliary system to the traditional physical attendance education, and this during the period of universities reopening, after the relative decline in the coronavirus infections number, from the point of view of a sample of university students.The study is based on a descriptive approach in the theoretical aspect, and on the questionnaire in the applied aspect of the study.The study results found that there is a weakness in e-learning service quality, according to the opinion of 200 students who were questioned through the axes covered by the questionnaire.